The Earliest East Slavic Liturgical Service for the Translation of the Relics of St. Nicholas of Myra (9 May) as an Adaptation of the Byzantine Liturgical Service for the Translation of the Relics of St. Bartholomew the Apostle (24 August) - Темчин, Сергей Юрьевич Юрьевич (Slavistica Vilnensis, 2015)
The author argues that the East Slavic liturgical service for the translation of the relics of St. Nicholas of Myra (9 May), which contains a Slavonic acrostic, is merely an adaptation of the Slavonic version of the Byzantine liturgical service for the translation of the relics of St. Bartholomew the Apostle (24 August), presumably composed by Joseph the Hymnographer. In the canon, no more than 6 troparia out of the total number of 28 are quite original compositions and do not depend on the above Byzantine model. Since the East Slavic service, like its Byzantine model, contains the minimum of stichera, it can be dated to the initial stage in the development of the Old East Slavic hymnography.
Keywords: Old Church Slavonic hymnography; Old East Slavic literature; translation of the relics of St Nicholas of Myra; translation of the relics of St Bartholomew the Apostle; Joseph the Hymnographer